2018
DOI: 10.3390/ma11030452
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Nanostructured Tantalum by Thermal-Mechanical Ultrasonic Impact Energy

Abstract: Microstructural evolution and wear performance of Tantalum (Ta) treated by ultrasonic nanocrystalline surface modification (UNSM) at 25 and 1000 °C were reported. The UNSM treatment modified a surface along with subsurface layer with a thickness in the range of 20 to 150 µm, which depends on the UNSM treatment temperature, via the surface severe plastic deformation (S2PD) method. The cross-sectional microstructure of the specimens was observed by electron backscattered diffraction (EBSD) in order to confirm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Furthermore, the fretting wear resistance was improved, so the technique may be useful for extending the lifespan of aircraft and nuclear components [12]. The technique was also used for the treatment of tantalum of a rather high purity [15]. The treatment caused both an increase in hardness and induced compressive residual stress.…”
Section: This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the fretting wear resistance was improved, so the technique may be useful for extending the lifespan of aircraft and nuclear components [12]. The technique was also used for the treatment of tantalum of a rather high purity [15]. The treatment caused both an increase in hardness and induced compressive residual stress.…”
Section: This Special Issuementioning
confidence: 99%
“…The effect was particularly pronounced at high material temperature upon sonification. A plastically deformed layer with the refined nano-grains was observed and correlated to enhanced wear resistance [15].…”
Section: This Special Issuementioning
confidence: 99%
“…Ultrasonic processing methods have been applied in many homogeneous and heterogeneous reactions for agitating or homogenizing solutions. Ultrasound can generate strong thermal [ 22 ], mechanical [ 23 ], and super-mixing effects [ 24 ], as well as cavitation phenomenon [ 25 ]. Cavitation is the formation, growth, and implosive collapse of bubbles in a liquid [ 26 ], which can further homogenize the particles on a microscopic scale [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lu has suggested that a gradient nanostructured material can improve both the strength and ductility compared to the nanostructured one [ 31 ]. Hence, it is suggested to generate a gradient nanocrystal structure using the UNSM process, which may lead to a further increase in both the strength and ductility [ 32 ]. Metallic materials are ductile, and they have a relatively lower strength but a relatively higher toughness or energy to failure because of greater ductility/post yield deformation.…”
Section: Resultsmentioning
confidence: 99%